1985
DOI: 10.1139/o85-096
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ation of chromatin: kinetics of relaxation and its effect on chromatin solubility

Abstract: We have studied the kinetics of relaxation of poly(ADP-ribosyl)ated polynucleosomes produced by endogenous enzyme activity by comparing the generation of hyper(ADP-ribosyl)ated histone H1 and its effect on the chromatin structure as revealed by electron microscopy. A correlation can be established between the appearance of histone H1 modified forms and the localized relaxation of the chromatin. We have also noticed, in parallel, that poly(ADP-ribosyl)ated chromatin showed increased solubility in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Thirty years ago, studies suggested that the large quantity of NAD ϩ synthesis taking place in the nucleus is involved in modulation of the chromatin structure (25,103,127,323; reviewed in reference 93). Chromatin or histone components, and to a lesser extent the nonhistone HMG proteins, are subject to a wide variety of covalent, reversible posttranslational modifications, such as acetylation; mono-, di-, and trimethylation on lysine residues; symmetric or asymmetric mono-and dimethylation on arginine residues; phosphorylation on serine and threonine residues; ubiquitination, biotinylation, and SUMOylation on lysine residues; and mono-ADP-ribosylation on arginine and glutamate residues (reviewed in references 40, 74, 137, 160, 177, 201, 413, and 420).…”
Section: Epigenetic Modification Of Histonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty years ago, studies suggested that the large quantity of NAD ϩ synthesis taking place in the nucleus is involved in modulation of the chromatin structure (25,103,127,323; reviewed in reference 93). Chromatin or histone components, and to a lesser extent the nonhistone HMG proteins, are subject to a wide variety of covalent, reversible posttranslational modifications, such as acetylation; mono-, di-, and trimethylation on lysine residues; symmetric or asymmetric mono-and dimethylation on arginine residues; phosphorylation on serine and threonine residues; ubiquitination, biotinylation, and SUMOylation on lysine residues; and mono-ADP-ribosylation on arginine and glutamate residues (reviewed in references 40, 74, 137, 160, 177, 201, 413, and 420).…”
Section: Epigenetic Modification Of Histonesmentioning
confidence: 99%
“…Over 20 years ago, high-resolution electron microscopy elegantly demonstrated that poly-ADP-ribosylated chromatin adopts a more relaxed structure than its native counterpart (25,103,127,222,323). When isolated polynucleosomes of interphase chromatin were poly-ADP-ribosylated in vitro by a highly purified preparation of PARP-1 at low and moderate ionic strengths, the solenoid structure (30-nm fiber) unwound into the 10-nm fiber and adopted the fully extended "beadson-a-string" structure characteristic of H1-depleted chromatin (25,103,323).…”
Section: Adp-ribosylation-mediated Changes In Chromatin Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its function as a coactivator/corepressor exchange factor, PARP1 has been also described to act as a structural component of chromatin and as a modulator of chromatin structure through its poly-ADP-ribosylation activity. Over 20 years ago, several studies provided evidence that poly-ADPribosylated chromatin adopts a more relaxed structure than its native counterpart (100,152,(218)(219)(220)(221)(222)(223)(224). When isolated polynucleosomes of interphase chromatin were poly-ADPribosylated in vitro by a highly purified preparation of PARP1 at low and moderate ionic strengths, the solenoid structure (30-nm fiber) decondensated into the 10-nm fiber and adopted the fully extended `beads on a string' structure characteristic for H1-depleted chromatin (100,218,221,222,224).…”
Section: Modulation Of the Chromatin Structurementioning
confidence: 99%
“…The decrease in DNAbinding affinity caused by electrostatic repulsion between DNA and poly(ADP-ribose) (PAR) as a result of the pos-translational modification may explain the reduction on the catalytic activity of some DNA-binding proteins [57,58]. Modification of other nuclear proteins such as nucleosomal proteins may also allow the access of various replicative and repair enzymes that bind specifically to those regions of the DNA containing strand breaks [59,60]. Telomeric repeat binding factor-1 Table 3.…”
Section: Roles Of Parp In Cellular and Molecular Processesmentioning
confidence: 99%